Technology Acceptance Model for Reconstructing Al-Islam and Kemuhammadiyah Learning at Universitas Muhammadiyah Sumatera Utara - Fanreza, Robie; Daulay, Mahmud Yunus; Ginting, Nurman (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study aims to see the influence of Usability Perception, Ease of Use, Attitude, and Behavioral Intention on Technology-Based AIK Learning in Universitas Muhammadiyah Sumatera Utara. Technology is currently an indicator of the development of science. Currently, Universitas Muhammadiyah Sumatera Utara continues to try to develop technology-based learning media towards a world-class university. However, many students are still not maximized with running the technology prepared for teaching, especially in AIK courses. This study uses a quantitative approach, hypothesis testing, and the inner model obtained from data processing using SMART PLS.  The conclusion are this study the t-statistic value for variable X1 (perceived usefulness) indicates that perceived convenience does not affect technology-based AIK learning, and the t-statistic value for variable X2 (Ease of Use) indicates that ease of use does not affect technology-based AIK learning. So, the t-statistic value for variable X3 (Attitude) indicates that attitude affects technology-based AIK learning. The t-statistic value for variable X4 (Behavioral Intention) indicates that Behavioral Intention affects technology-based AIK learning. The Technology Acceptance Model (TAM) explains how users accept and adopt technology based on two main factors: perceived usefulness and perceived ease of use. In the context of AIK learning at Universitas Muhammadiyah Sumatera Utara (UMSU), TAM plays a crucial role in shaping the effectiveness and efficiency of technology-based learning.